A survey of hospital healthcare professionals' perceptions toward patient safety culture in Saudi Arabia - Farhan Alshammari; Eddieson Pasay-an; Mohammad Alboliteeh; Mohammed Hamdan Alshammari; Tantut Susanto; Sandro Villareal; Maria Charito Laarni Indonto; Ferdinand Gonzales (Elsevier, 2019)
Background: Medical and allied health professionals should adopt error reduction as a key strategic priority and make patient safety improvement an ongoing, active process within their organization. Objective: The present study investigates the perceptions of healthcare professionals toward patient safety culture in hospitals throughout Hail Region, Kingdom of Saudi Arabia. Methods: This research, which uses a descriptive cross-sectional approach to evaluate the perceptions of healthcare professionals toward patient safety culture, was conducted at four major hospitals in Hail Region, Kingdom of Saudi Arabia and involved 255 healthcare professionals, who served as respondents based on systematic random sampling. Standard deviation and the chi-square test of independence were used for statistical analysis. This study was approved by the Ethics Review Committee (H-2016-057) of the University of Hail. Results: Among the patient safety aspects, patient safety grade received the highest mean value (3.56 ± 0.72), whereas handoffs and transitions received the least consensus (3.00 ± 0.34). Interestingly, hospital work experience significantly correlated to work area (p = 0.026), communications (p = 0.037), and the number of events reported (p = 0.019) in the patient safety dimension. Moreover, the number of years in the area/unit significantly related to the work area (p = 0.047) and supervisor/manager (p = 0.009). Only the number of events reported showed a significant relationship with specialty or profession (p = 0.007). Conclusion: Healthcare professionals have an affirmative view toward patient safety culture aspects, and positive relationships were found between the patient safety dimensions and study participants' profile. The findings presented herein suggest that healthcare professionals affirm the practice of patient safety culture. However, further research is required to continuously appraise the significance of healthcare-based quality indicators. Overall, the assessment results suggest a platform for better intervention and transformation procedures targeting the promotion of patient safety culture. Keywords: Patient safety culture, Healthcare professionals, Healthcare organizations, Patient safety